THE ASSOCIATIONS IN HOLGUIN DURING THE YEARS 1940-1950 (Retracted document) - Hernández Basulto, Osmany (2019)
RETRACTATION NOTE The Editorial Board of the Journal of Social Sciences of the University of Costa Rica, has retracted the publication of the article "The  associations in Holguin during the years 1940-1950" presented by the authors Osmany Hernández Basulto and Isel Ramírez Berdut, which was published in number 164 (II-2019) because five pages of such an article are a literal copy of the first chapter of the book Sociability and culture of leisure: The Havana elite and their recreational clubs (Havana: Fundación Fernando Ortiz, 2009 ) by the author Maikel Fariñas Borrego. The objective of this article is to show that the members to such organizations in HolguínCity during the period between 1940 to 1950, belonged to the most economically welloffclasses in the city, a favorable condition for proposing and developing public actionsin the municipal council —from private initiatives— with repercussions on the utilityservices sector, as well as trying to solve some problems of everyday life. These membersinvolved in their actions to plenty of neighbors for the improvement and recognitionof the city as one of the most important in Oriente Province. For the elaborationof this article, the methodology used has privileged the qualitative paradigm, using methods of the theoretical level, among which are: 1) logical and inductive-deductive,for the interpretation of the information; 2) analysis and criticism of sources, takingas a procedure the methods of logic-historic thought applied to sources consulted; 3)hermeneutic-literary method , used to make inferences from the consulted documentation.